(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This study presents detailed energy efficiency and emission calculations for five major thermal power stations in Uzbekistan, quantifying their current performance, fuel consumption patterns, CO₂ emission levels, and improvement potential. Uzbekistan’s power sector relies heavily on natural gas-fired thermal generation, with approximately 90% of national electricity produced by thermal power stations (IES), many of which were commissioned during the Soviet era and operate below design efficiency. Using plant-level operational data, thermodynamic heat balance analysis, and IPCC emission factor methodology, this study calculates the specific fuel consumption (SFC), thermal efficiency, and CO₂ emission intensity for each station. Results reveal that the analyzed stations operate at thermal efficiencies of 28–42%, with SFC values ranging from 290 to 430 g.c.e./kWh, and emission intensities of 520–780 kg CO₂/MWh. Modernization scenarios demonstrate that upgrading aging equipment and implementing combined cycle technology could improve fleet-average efficiency from 33.4% to 48.5%, yielding annual fuel savings of 3.2 billion m³ of natural gas and CO₂ emission reductions of 12.8 million tonnes. These calculations provide a quantitative basis for investment prioritization and energy policy planning in the Uzbekistan power sector